Menantang Humanisme; Perspektif Al-Qur`an Terhadap Penerapan Pidana Mati Bagi Pengedar Narkotika - Sulhi M Daud; M. Iqbal Bafadhal; Mohamad Rapik (Fakultas Hukum, Universitas Jambi, 2023)
This article aims to explore the concept of humanism from the application of the death penalty against narcotics dealers and to find out the response of the Qur'Än with respect to the application of the death penalty. This article employs a literature review, namely a type of research whose legal sources are available in libraries and digital access, which is normative research with a qualitative-descriptive approach. The research results show that the textual meaning of the verses of the Qur'Än for narcotics dealers can be categorized as a form of destructive action (fasÄdan fÄ« al-ardhi) belonging the ta'zÄ«r punishment where the right to pardon and claim leniency in court is still open. However, contextually the verses for narcotics dealers can be categorized into various punishment provisions, namely based on the á¸¥irÄbah (robbery) verse where the perpetrator is sentenced to death, if the narcotics dealer does it to take wealth by deception and violence. Also based on the verse al-baghyu (rebellion) with the threat of the death penalty, if narcotics traffickers do it politically with the aim of chaos and disturbing state security and/or taking over legitimate power/government, based on the verse drinking wine (shirb al-khamr), if Narcotics dealers are sentenced to death as recidivists who have been punished several times, as are repeat al-khamr drinkers up to 4 times who are sentenced to death. With several alternative applications of punishment, a reflection of the humanism of the Qur'Än can be observed clearly. Abstrak Artikel ini bertujuan untuk mengetahui konsep humanisme dalam bentuk penerapan hukuman mati pada pengedar narkotika dan mengetahui respons al-Qur`an dalam menyikapi penerapan hukuman mati tersebut. Artikel ini menggunakan studi literatur (literature review), yaitu jenis penelitian yang sumber hukumnya sudah tersedia di perpustakaan dan akses digital, yang bersifat penelitian normatif dengan pendekatan kualitatif-deskriptif. Hasil penelitian menunjukkan bahwa secara makna tekstual ayat al-Qur`Än untuk pengedar narkotika dapat dikategorikan sebagai makna fasÄdan fÄ« al-ardhi dalam ranah hukuman taâ€™zÄ«r yang masih terbuka hak grasi dan penuntutan keringanan hukuman di pengadilan. Namun secara kontektual ayat bagi pengedar narkotika dapat dikategorikan ketentuan hukumannya secara beragam yaitu berdasarkan ayat á¸¥irÄbah (perampokan) di mana pelaku dipidana mati, jika pengedar narkotika melakukannya untuk mengambil kekayaan dengan cara tipuan dan kekerasan. Juga berdasarkan ayat al-baghyu (pemberontakan) dengan ancaman pidana mati, jika pengedar narkotika melakukannya secara politis dengan tujuan kekacauan dan mengganggu keamanan negara dan/atau mengambil alih kekuasaan/pemerintahan yang sah, berdasarkan ayat peminum khamar (syirb al-khamr), jika pengedar narkotika dipidana mati sebagai residivis yang telah dihukum beberapa kali sama halnya dengan peminum al-khamr yang berulang sampai 4 kali untuk dipidana mati. Dengan beberapa alternatif penerapan hukuman itulah, refleksi humanisme al-Qurâ€™an terlihat.